APPROACHES TO DEVELOPING FUTURE INFORMATICS TEACHERS' COMPETENCE IN ARTIFICIAL INTELLIGENCE - Najmetdinova Nargiza Sayfetdinovna (Modern American Journals, 2025)
This article analyzes didactic approaches aimed at forming and developing the competence of future informatics teachers in artificial intelligence (AI). Modern concepts of AI competence for teachers proposed by UNESCO and other international organizations, as well as models and documents such as the AI CFT (AI Competency Framework for Teachers), are taken as a scientific and theoretical basis. The study presents the results of a diagnostic questionnaire conducted with the participation of future informatics teachers, an analysis of curricula and programs, as well as experimental work based on an integrated module on AI. The results indicate the need for specially designed teaching strategies, practical projects, and the integrated use of distance and blended learning technologies to develop knowledge, skills, and reflexive-reflective competencies in AI in future informatics teachers. At the end of the article, methodological recommendations are given on the systematic integration of AI components into the process of training computer science teachers in higher education institutions.
Keywords: Artificial intelligence, AI literacy, computer science teacher, future teacher, competence, AI CFT, digital pedagogy.